ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN BUAH APEL FUJI (Studi Kasus: Toko Buah King Fresh Kota Samarinda): ANALYSIS OF FACTORS INFLUENCING CONSUMER DECISIONS IN PURCHASING FUJI APPLES (Case Study: King Fresh Fruit Shop Samarinda City) - Arief Rahman; Nella Naomi Duakaju; Mursidah (Universitas Widya Gama Mahakam, 2023)
Imported apples are apples imported from abroad, there are several types that have been circulating in the market such as USA red apple and Fuji apple. This study aims were to determine the characteristics of consumers who buy fuji apples, and to determine the factors that influence consumer decisions in purchasing fuji apples. This research was conducted at King Fresh Fruit Store in Samarinda City from April to June 2022. The data used in the form of primary data collected through questionnaires and secondary data obtained from sources such as journals, BPS data, books and other literature that supports the research. Sampling used a non-probability sampling method with accidental sampling technique and the number of samples was 40 respondents. The data obtained were analyzed using descriptive analysis and logistic regression at the level of 5%. The results of this study indicated that the characteristics of consumers who buy Fuji apples are dominated by women, age range 15-64 years, high school education level/equivalent, have 3-4 family members, and have jobs as household workers and entrepreneurs. While the factors that influence consumer decisions in purchasing Fuji apples are price, taste, size and texture/crisp which have a significant effect on consumer decisions with a significance value of < 0.050. While the factors that do not influence consumer decisions in purchasing Fuji apples are color, freshness, income, number of family members, education level, benefits, and availability.